2003
DOI: 10.1002/bem.10143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electromagnetic field emitted by cellular phones on the EEG during an auditory memory task: A double blind replication study

Abstract: The effects of electromagnetic fields (EMF) emitted by cellular phones on the event related desynchronization/synchronization (ERD/ERS) of the 4-6, 6-8, 8-10, and 10-12 Hz electroencephalogram (EEG) frequency bands were studied in 24 normal subjects performing an auditory memory task. This study was a systematic replication of our previous work. In the present double blind study, all subjects performed the memory task both with and without exposure to a digital 902 MHz field in a counterbalanced order. We were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 24 publications
3
87
1
Order By: Relevance
“…Their findings indicated that EMF decreased the theta band activity only during their memory retrieval task, and increased the alpha band activity. However, a replication study by Krause et al [2004] did not confirm these findings.…”
Section: Introductionmentioning
confidence: 82%
“…Their findings indicated that EMF decreased the theta band activity only during their memory retrieval task, and increased the alpha band activity. However, a replication study by Krause et al [2004] did not confirm these findings.…”
Section: Introductionmentioning
confidence: 82%
“…Some studies of human cognitive functioning have shown that exposure to electromagnetic fields of the type emitted by mobile phones can affect cerebral functions (e.g., Hamblin et al, 2004) as well as the behavioral performance of exposed volunteers (e.g., Keetley et al, 2006;Koivisto et al, 2000). Other studies, however, have found no significant effects either on human behaviour (Russo et al, 2006;Haarala et al, 2004), or on brain processes (e.g., Krause et al, 2003).…”
mentioning
confidence: 99%
“…Some of the studies indicated that EMF caused a reduction in the voltage of slow potentials. However, a more detailed analysis of the results and their verification in further experiments did not confirm the earlier observations [12][13][14]. Considering the limitations of the EEG method, in our current work we decided to use determinations of P300 wave to assess EMF effect on auditory cortex ERPs.…”
Section: Discussionmentioning
confidence: 79%